Mechanical Evaluation of Bone–Patellar Tendon–Bone Graft Fixation to the Tibia in ACL Reconstruction: Bone Plug Tensioning and Fixation System versus Interference Screw - Iuchi, Ryo; Shino, Konsei; Mae, Tatsuo; Yamakawa, Satoshi; Nakata, Ken (The Journal of Knee Surgery, 2024)
This study aimed to evaluate the mechanical properties of bone plug fixation to the tibia with a novel device, the Bone plug Tensioning and Fixation (BTF) system.Forty bone–tendon–bone grafts consisting of the whole patella–patellar tendon–tibial bone plug of 10-mm width and tibiae from the porcine were prepared. After creating a 10-mm tibial tunnel, the tibial bone plug was fixed to the tibia with the BTF system or the interference screw (IFS) to prepare a test specimen of the patella–patellar tendon–tibial bone plug fixed to the tibia. For the graft tension controllability study, a predetermined initial tension of 9.8 or 19.6 N was applied and maintained for 5 minutes. Then the bone plug was fixed to the tibia with the BTF system or IFS in 10 specimens, monitoring the residual tension for an additional 5 minutes. Then, a cyclic loading test and a tension-to-failure test were performed.The mean difference between the residual tension and the predetermined tension was significantly smaller in BTF fixation (9.8 N → 10.6 ± 2.2 N; 19.6 N → 18.9 ± 2.1 N) than in IFS fixation (9.8 N → 23.4 ± 7.4 N; 19.6 N → 28.9 ± 11.5 N). The mean displacement of the bone plug after cyclic loading was significantly less in the BTF group (1.2 ± 0.6 mm) than in the IFS group (2.2 ± 1.0 mm; p < 0.01). Stiffness was significantly greater in the BTF group (504.6 ± 148.8 N/mm) than in the IFS group (294.7 ± 96.7 N/mm; p < 0.01), whereas the maximum failure loads in the two groups did not differ significantly (724.2 ± 180.3 N in the BTF and 634.8 ± 159.4 N in the IFS groups).BTF system better performed in graft tension controllability than IFS did. BTF fixation was superior to IFS fixation in the displacement of the bone plug during the cyclic loading test and in stiffness in the tension-to-failure test.
Keywords: ACL reconstruction; BTB graft; graft tension; graft fixation; tibial fixation device; bone plug tensioning and fixation system